The Architecture of Markets: An Economic Sociology of Twenty-First-Century Capitalist Societies (translated by Alexander Kurakin) - Fligstein, Neil (Journal of Economic Sociology, 2013)
Market societies have created more wealth and more opportunities for more people, than any other system of social organization in history. Yet we still have a rudimentary understanding of how markets themselves are social constructions that require extensive institutional support. This groundbreaking work seeks to fill this gap, to make sense of modern capitalism by developing a sociological theory of market institutions. Addressing the dynamism that capitalism brings with it, Neil Fligstein argues that the basic drift of any market and its actors is toward stabilization. “The Architecture of Markets” represents a major and timely step beyond recent, largely empirical studies that oppose the neoclassical model of perfect competition but provide sparse theory toward a coherent economic sociology. Fligstein offers this theory. His political-cultural approach explains why governments remain crucial to markets and why so many national variations of capitalism endure. States help make stable markets possible by, for example, establishing the rule of law and adjudicating the class struggle. State-building and market-building go hand in hand. Fligstein shows that market actors depend mightily upon governments and the members of society for the social conditions that produce wealth. He demonstrates that systems favoring more social justice and redis¬tribution can yield stable markets and economic growth as readily as less egalitarian systems. The journal publishes the chapter 9, «Globalisation», excerpt from «The Architecture of Markets» by Neil Fligstein. The author questions why increasing globalisation has not resulted in convergence of organisational forms at national level. In search of an answer to this puzzle, Fligstein uses the analytical tools of a politicalcultural approach. As the main tasks of the chapter the author considers the development of working definitions of globalisation and a review of arguments demonstrating that globalists exaggerate the scope of its impact on the organisation of production, the state’s role in providing for their citizens and social stratification.